(untitled) (Revista Innova Educación, 2024)
The provision of educational services in rural contexts requires educational leadership that addresses the demands of an educational community based on its geographical and social characteristics. In this context, the research aimed to explore the relationship between pedagogical leadership and the territorial approach a group of rural directors of public educational institutions in the Ayacucho region, Perú. A phenomenological qualitative study was conducted, using semi-structured interviews with a group of five directors of rural public schools. Among the main results, it was found that efficient exercise of pedagogical leadership allows directors to construct solutions that favor the educational quality of the institution. It was also identified that the role of pedagogical leadership in rural schools implies a series of challenges, such as efficient preparation in the management of human and material resources, as well as proactive management of relationships with the educational community based on their characteristics and needs. It is concluded that efficient knowledge of the territorial approach by directors reinforces their educational leadership, encouraging the participation of students, teachers, families, local and regional authorities to provide the necessary support and assistance required by the educational community in the rural area.